Research on motion and friction of rolling piston in rotary compressor. Issue 1 (September 2021) - Xu, J; Yu, B; Yang, O X; Ding, S P; Zhao, H H
Abstract: Based on the Reynolds equation of mixed lubrication, the dynamic model of rolling piston was established, and the axis locus, rotation velocity, sliding velocity at vane tip, and friction loss of the piston were numerically solved. The analysis results indicated that the numeric results of sliding velocity at vane tip are in good agreement with the experimental results. In addition, the influences of crankshaft rotation speed, working condition, piston density and compression structure parameters on motion and friction were analyzed. Taking the ratio of piston rotation velocity and revolution velocity (λ) as evaluation index, whether λ conforms to cosine curve can judge the motion state between piston and vane. The results show that there is not only sliding state but also rolling state between piston and vane tip, and keeping rolling state is helpful to reduce friction loss. The design schemes of lighter piston, thicker vane and larger height-diameter ratio cylinder are proposed to keep rolling state in a wider rotation speed range and smaller pressure difference condition, thereby improving the annual operating efficiency of R32 rotary compressor.